2019
DOI: 10.1002/eqe.3209
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance and design of bridge column‐to‐pile shaft pipe‐pin connections in precast and cast‐in‐place bridges

Abstract: Summary Hinge or “pin” connections may be used in integral bridges to connect columns to pile shafts to reduce the foundation force demand. Used in combination with prefabricated columns, pins facilitate accelerated bridge construction (ABC). These innovative methods could improve the quality and economy of project compared with conventional construction in seismic regions. This study developed pipe pins that reduce moment transfer between the column and pile shaft under seismic excitations. The pipe pins cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…These components include: external energy dissipation) ED) devices as shown in Figure 5(i), (j), and (k) (Andisheh et al, 2018; Chou and Chen, 2005; Marriotte et al, 2009; ElGawady and Sha’lan 2011; Marriotte et al, 2009), external ED devices with a pocket connection, in which the precast RC column is inserted into a pocket located in precast RC footing, as shown in Figure 5(d) (Currie et al, 2007), internal longitudinal ED bars, as shown in Figure 5(g) (Jia et al, 2020; Jia et al, 2022; Ou et al, 2010; Ou et al, 2018), internal ED bars and CIP grout, as shown in Figure 5(a) (White and Palermo, 2016), and internal ED bars with concrete/steel shear keys as shown in Figure 5(h) (Hung et al, 2017). In addition, Mehrsoroush and Saiidi (2016), Mehraein & Saiidi. (2019), and Mehrsoroush & Saiidi.…”
Section: Constructionmentioning
confidence: 99%
“…These components include: external energy dissipation) ED) devices as shown in Figure 5(i), (j), and (k) (Andisheh et al, 2018; Chou and Chen, 2005; Marriotte et al, 2009; ElGawady and Sha’lan 2011; Marriotte et al, 2009), external ED devices with a pocket connection, in which the precast RC column is inserted into a pocket located in precast RC footing, as shown in Figure 5(d) (Currie et al, 2007), internal longitudinal ED bars, as shown in Figure 5(g) (Jia et al, 2020; Jia et al, 2022; Ou et al, 2010; Ou et al, 2018), internal ED bars and CIP grout, as shown in Figure 5(a) (White and Palermo, 2016), and internal ED bars with concrete/steel shear keys as shown in Figure 5(h) (Hung et al, 2017). In addition, Mehrsoroush and Saiidi (2016), Mehraein & Saiidi. (2019), and Mehrsoroush & Saiidi.…”
Section: Constructionmentioning
confidence: 99%
“…2(d)] was obtained by replacing the UHPC a mortar bed with ECC material. The ECC material was used because of its high damage tolerance and enhanced ductility, as discussed by Li and Zhang (2011) and Mehraein and Saiidi (2019). These advantages potentially contribute to the resistance to contact damage at the rocking surface.…”
Section: Enhanced Solutions and Designmentioning
confidence: 99%
“…(1) e soils used for this simulation analysis are the foundation pit soils of a station on the Yushu Expressway (Gongyu Expressway) in the plateau permafrost area. e length of the foundation pit is 234.7 m, the width of the standard section is 20.7 m, the buried depth of the bottom plate is about 17.74-19.25 m, and the buried depth of the Fushi is 3.9 m. e ground depth of the test soil sample is about 7-9 m. e soil sample taken from the foundation pit will be exposed to the sun, crushed, and screened, and a variety of soil samples will be selected as the frozen soil for the static and dynamic strength and dynamic parameter tests and the dynamic characteristics tests of the model pile foundation in the subsequent frozen soil environment [20][21][22][23][24][25][26].…”
Section: Source Of Simulation Data and Experimental Environment Settingsmentioning
confidence: 99%